Pengaruh Penurunan Tarif Pajak dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Dengan Sosialisasi Perpajakan Sebagai Variabel Moderasi - Kamila Windyani Putri; Marhusin; Nur Hajijah (JURNAL BISNIS DAN PEMBANGUNAN, 2025)
Abstract: This study aims to analyze the effect of tax rate reduction and tax sanctions on the compliance of individual taxpayers engaged in Micro, Small, and Medium Enterprises (MSMEs), with tax socialization as a moderating variable. The Theory of Planned Behavior (TPB) is used as the theoretical framework to explain taxpayer behavior based on attitudes, subjective norms, and perceived behavioral control. The research applies a quantitative approach with data collected from individual MSME taxpayers registered at KPP Pratama Banjarmasin. Sampling was determined using the Slovin formula, and data were analyzed through regression testing and Moderated Regression Analysis (MRA). The results indicate that both tax rate reduction and tax sanctions have a significant influence, which is further moderated by tax socialization in improving taxpayer compliance. Effective tax socialization strengthens the relationship between the independent variables and taxpayer compliance by increasing understanding, awareness, and perception of fairness. These findings provide practical implications for the Directorate General of Taxes (DGT) in developing fair and sustainable tax policies that encourage voluntary compliance through continuous education and outreach